Versatile parallel signal processing with a scalable silicon photonic chip - Shihan Hong; Jiachen Wu; Yiwei Xie; Xiyuan Ke; Huan Li; Linyan Lyv; Yingying Peng; Qingrui Yao; Yaocheng Shi; Ke Wang; Leimeng Zhuang; Pan Wang; et al. (Nature Communications)
Abstract Silicon photonic signal processors promise a new generation of signal processing hardware with significant advancements in processing bandwidth, low power consumption, and minimal latency. Programmable silicon photonic signal processors, facilitated by tuning elements, can reduce hardware development cycles and costs. However, traditional programmable photonic signal processors based on optical switches face scalability and performance challenges due to control complexity and transmission losses. Here, we propose a scalable parallel signal processor on silicon for versatile applications by interleaving wavelength and temporal optical dimensions. Additionally, it incorporates ultra-low-loss waveguides and low-phase-error optical switch techniques, achieving an overall insertion loss of 10 dB. This design offers low loss, high scalability, and simplified control, enabling advanced functionalities such as accurate microwave reception, narrowband microwave photonic filtering, wide-bandwidth arbitrary waveform generation, and high-speed parallel optical computing without the need for tuning elements calibration. Our programmable parallel signal processor demonstrates advantages in both scale and performance, marking a significant advancement in large-scale, high-performance, multifunctional photonic systems.